Determination of Narasin in Chicken Fat: A Bridging Study Comparing the Bioautographic Method (FSIS CLG Method R22) to a Liquid Chromatography with Tandem Mass Spectrometry Method (AOAC Method 2011.24). (27th November 2019) - Mizinga, Kemmy M; Burnett, Thomas J; Brunelle, Sharon L; Wallace, Michael A; Coleman, Mark R
Abstract: Lilly Method AM-AA-CA-R108-AB-755, which is substantially the same as U.S. Department of Agriculture, Food Safety and Inspection Service (FSIS) Chemistry Laboratory Guidebook (CLG) method R22, is the current regulatory method for determining narasin in cattle and chicken tissues and is based on bioautography, creating a zone of inhibition of bacterial growth, with the size of the zone correlating to the amount of narasin extracted from the tissue. AOAC Method 2011.24 is an LC-tandem mass spectrometry (MS/MS) method for determining narasin content from bovine, swine, or chicken tissues. It has many advantages over the regulatory method, including higher throughput, less solvent use, no use of carbon tetrachloride, a wider method range, inclusion of swine tissues, and it is less labor intensive. In this study, AOAC Method 2011.24 was compared to FSIS CLG method R22 for the determination of narasin in chicken abdominal fat. Fortified chicken-fat samples ranging from 20 to 960 ng/g and incurred chicken-fat samples ranging from 40 to 480 ng/g were assayed by both methods in triplicate. Mean accuracies for the two methods were similar, 77–110% for CLG R22 and 84–96% for AOAC Method 2011.24, and the method results showed a linear correlation. The methods differed in precision, however, with the CLG R22 method yielding 2.6–34% RSD and AOAC Method 2011.24 yielding 0.15–6.4% RSD. It is recommended that AOAC Method 2011.24–granted AOAC Official Method SM Final Action status—be adopted as the official U.S. regulatory method.